Experimental investigations of a micro roller hot embossing process for polymer-based microfluidic device fabrication - Thang, Van Sang. (2011)
A micro roller hot embossing process creates microstructures and patterns on polymeric materials for polymer-based microfluidic device fabrication. In this process, a polymeric material is preheated in the preheat chamber and subsequently passes through embossing interface between the two rollers. The internally heated flexible mold that is tightly wrapped around the top roller provides a progressive line contact with the substrate at the embossing interface and the mold features are transferred onto it under applied pressure. This thesis reports the results of experimental investigations of micro roller hot embossing process. Flexible nickel mold with different pattern designs and polymethyl methacrylate (PMMA) as a substrate material were used in the experiments. Design of Experiments based on Box-Behnken Design was performed and the influences of process parameters on the depths of embossed channels were systematically investigated. Design Expert software was used to employ Response Surface Methodology for analyzing and optimizing the process parameters. The experimental processes reveal that great potential for mass production of microfluidic device fabrication is possible with successful implementation of micro roller hot embossing process. A short duration of less than one minute is sufficient to fabricate different patterns of microstructures on polymeric substrate material.